1977
DOI: 10.1148/125.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoadenoma and Focal Nodular Hyperplasia: Pitfalls in Radiocolloid Imaging

Abstract: Both hepatoadenoma and focal nodular hyperplasia must be considered in the differential diagnosis of right upper quadrant pain or mass in young women taking oral contraceptives. Three new cases are presented, and the radionuclide scan findings of 35 additional cases reviewed. There is great variability in the radiocolloid liver scans of these entities. Hepatoadenomas often develop along the inferior margin of the liver, and may therefore go undetected by radiocolloid imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Unfortunately, only the minority of FNH show this feature of increased or normal uptake of sulfur colloid; the majority do not accumulate colloid material and therefore display defects by static imaging. Approximately one-third of patients with FNH manifest increased or normal colloid uptake [5,28]. This fact perhaps indicates that the activity or number of Kupffer cells in FNH is variable because foci of hemorrhage and necrosis, which could explain the decreased radionuclide uptake, are uncommon in this lesion [5,7,17].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only the minority of FNH show this feature of increased or normal uptake of sulfur colloid; the majority do not accumulate colloid material and therefore display defects by static imaging. Approximately one-third of patients with FNH manifest increased or normal colloid uptake [5,28]. This fact perhaps indicates that the activity or number of Kupffer cells in FNH is variable because foci of hemorrhage and necrosis, which could explain the decreased radionuclide uptake, are uncommon in this lesion [5,7,17].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, this was attributed to the absence of Kupffer cells [ 81 ]. However, a recent pathological study demonstrated that all hepatic adenomas studied contained Kupffer cells.…”
Section: Hepatocellular Adenomamentioning
confidence: 95%